FAKTOR-FAKTOR YANG BERHUBUNGAN DALAM PEMILIHAN JENIS KONTRASEPSI EFEKTIF PADA WANITA PASANGAN USIA SUBUR DI WILAYAH KERJA PUSKESMAS RAWASARI KOTA JAMBI - Reni Gusdianita; Rahmah Rahmah; Yuliana Yuliana (Jurnal Akademika Baiturrahim Jambi, 2016)
Background:The choice of effective contraception is the aim of delaying pregnancy, controlling the birth rate and population growth in Indonesia. The sort of effective contraception consists of the birth control pill, injectable, implants and IUD. The women sometimes have difficulty in determining the type of contraception to be used due to low education and lack of knowledge about the benefits, side effects, indications and contra indications of the use of effective contraceptive. Attitude of family planning acceptors and support of husband also have a great influence on the choice of effective contraception.Method:This quantitative research used cross sectional.Taking of sample used throughProportional Random Sampling with total sample 105 respondents of 4 districts. Data was collectedthrough questionnaire from August 28th to September 7th 2015, having a visit to the house (door to door). Data was analyzed through univariate and bivariate with Chi-square with significance level 5%.Result of the research were obtained that education (p=0.001), knowledge (0.048), attitude (p=0.036), husband support (p=0.002), so it can be concluded that there was the significance correlation between education, knowledge, attitude, and husband support in the choice of effective contraception. It is suggested that the public health center Rawasari can provide information and counseling toward choice of effective contraception and side effects in the usage of contraception. As an input, for the next researcher can contribute and inform how to use other contraceptive methods. Keywords : education, knowledge, attitude husband ,choice of effective contraception